A Comparative Study on Land Rights of Peasants in China and Aboriginal Citizens in Canada and Their Impact on Development. Issue 2 (3rd May 2016) - Cheng, Hongming; Ma, Ling
Abstract : This article examines the relationships between land reform and socio-economic development in rural communities in China and in Aboriginal communities in Canada. Using statutes, legal cases, policy documents produced by government agencies and professional organizations in the two countries, as well as open-ended interviews in Zhejiang, China, and Saskatchewan, Canada, this study analyses the impact of land tenure arrangements on economic development and peasants' living standard and environment. Results suggest that, despite its positive effect on general rural and Aboriginal economic development, such development is compromised by several institutional hurdles that harm peasants' and Aboriginal citizens' interest. Both Chinese peasants and Aboriginal citizens face new forms of exploitation by governments and businesses.